Entropy Generation Analysis around Airfoil Using Multi-Block Lattice Boltzmann Method (Advances in Applied Mathematics and Mechanics, 2022)
This present paper proposes aerodynamic forces and entropy generationcharacteristics on the flow past two-dimensional airfoil at low Reynolds number bymultiple-relaxation-time lattice Boltzmann method to clarify the flow loss mechanism.The block mesh refinement was adopted in which a higher accuracy was needed inparts of the domain characterized by complex flow. The interpolated bounce-backmethod was used to treat the irregular curve. This numerical method can effectivelysolve the complex flow field simulation problems with reasonable accuracy and reliability by simulating flow around plate and airfoil. Based on second law of thermodynamics, an expression of entropy generation rate for arbitrary control volume wasderived theoretically which could accurately quantify the local irreversible loss of theflow field at any position. After that, a comprehensive numerical study was conductedto analyze relationship of entropy generation and drag force by taking NACA0012 airfoil as the research object. For unsteady condition, entropy generation rate and thedrag force are not linearly related any more. Losses due to steady effects mainly consider the irreversibility in the boundary layer and wake while the unsteady effectscome from the interaction between the main separation vortex and the trailing shedding vortex.